Emerging sanitation techniques for fresh-cuts - Alexandre, Elisabete M. C. (2017)
With fresh-cut fruits and vegetables being more and more highly appreciated by consumers, it is important to develop adequate processing procedures in order to ensure their fresh-like quality and nutritional value, and more importantly their microbial safety. The whole food chain, from field production, harvesting, processing, and distribution through to consumption, is important to achieve this goal. However, one of the most important steps is the treatment, after harvesting, used for the inactivation/growth inhibition of microorganisms. Most of the emerging sanitation techniques applied to fresh-cut fruits and vegetables, some already implemented at the industrial level and others still under pilot-scale testing, are critically reviewed. Its characteristics and impacts on microbial inactivation or inhibition, and the corresponding applications, are described in detail. Moreover, fields where there is a great need for further research are identified.